Optimized synergy in networked infrastructure deployment and maintenance: Optimizing the planning of infrastructure works and the synergies in the trench - Jonathan Spruytte; Mathieu Tahon; Koen Casier; Sofie Verbrugge; Didier Colle; Mario Pickavet (International Telecommunications Society (ITS), 2014)
Underground infrastructure installation is prevalent in Belgium and both maintenance and new installations will lead to large costs. Important reductions in these costs are possible by performing road works in synergy. Formerly the overhead of the cooperation and the limited IT tools and data available limited the operators view on possible synergies and made at the same time exploiting these synergies less obvious and more cumbersome. With the increase of detail in the geographical information bases containing all information on the installation per operator, synergies open up more opportunities and could lead to very important reductions in the operators' costs. In order to reap these benefits, a set of challenges should be overcome. This paper indicates how optimization tools on trench structure and GIS planning can aid in exploring this potential. The first approach indicates how the trench can be optimally organized in order to reduce trench depth, width or overall costs. The second approach indicates how existing planning of road works of several infrastructure owners can be mapped to each other. The planned road works can be rescheduled to optimize overlap between infrastructure owners and group smaller road works into larger chunks, still taking into account timing constraint initially set and keeping budget for each period under control. The combination of both optimizations will allow operators to optimally align their mid- and long-term planning and use an optimal trench, reducing costs. It also indicates which data should be shared and how the optimization should be performed.
Keywords: 330; Network deployment; scheduling; infrastructure networks; synergies